Hotel Booking System for Ridel Hotel Kota Bharu - Rahimi, Nurul Khairiyah (Applied Information Technology And Computer Science, 2022)
The purpose for this project is to develop a web-based hotel booking system for Ridel Hotel Kota Bharu. The project aims at upgrading and automating manual booking activities which is really inefficient and time-taking. Their current booking activities are quite far behind as they are still using manual system to handle booking processes. Every reservation details and guests information are still recorded in a book and files and those files will be stored in the cabinet near the counter. The bills is done manually too. For this hotel booking system project, it is actually not only it will secure the data far more better than the current manual system, but also can record much more detailed data of unlimited amount of guests. This hotel booking system will provide various of functionality to user and hotel receptionist. The activities regarding this system involve making a reservation/booking, room cancellation, new guest registration, room types and service, and total billing. This system will be developed as a website platform using structured analysis approach. Hopefully this Hotel Booking System will help to ease the problem that this hotel faces. Upgrading their booking system can make lot of advantage as it will increase the hotel’s efficiency and can save so much time. An easy and user-friendly booking system will attract more guests and this will increase the chance of reaching business goals.The hardware requirements that use in the developing the system is Acer Aspire ES 15 laptop, Intel® Celeron® Quad Core Processor N3160, 4 GB DDR3 L RAM (Random Access Memory), and 500 GB HDD hard drive, while for the software requirements used in building this propose system is Microsoft Windows 10, Hypertext Pre-Processor (PHP), Edraw Max, MySQL, XAMPP, Sublime Text 3.0, and phpMyadmin. Next, the interface design of the propose system are the homepage interface, login interface, registration interface, room catalogue interface, booking interface, and cancellation interface.